Characterization of key odor‐active compounds in sweet Petit Manseng (Vitis vinifera L.) wine by gas chromatography–olfactometry, aroma reconstitution, and omission tests. Issue 4 (17th March 2021) - Lan, Yibin; Guo, Jingxian; Qian, Xu; Zhu, Baoqing; Shi, Ying; Wu, Guangfeng; Duan, Changqing
Abstract : Abstract: Petit Manseng ( Vitis vinifera L.) has become a popular variety in China for the production of semisweet and sweet wines. However, few studies focused on investigating the molecular odor code of its key odorants. In this study, the key odor‐active compounds of Chinese sweet Petit Manseng wine were identified by gas chromatography–olfactometry (GC–O) and gas chromatography–mass spectrometry (GC–MS). Fifty‐five odorous zones were sniffed and identified by application of aroma extraction dilution analysis on a distillate prepared by liquid–liquid extraction and solvent‐assisted flavor evaporation. Among them, isoamyl alcohol, ethyl octanoate, isovaleric acid, (E)‐β‐damascenone, and phenylethanol particularly displayed with highest flavor dilution factors above 1024. The quantification of volatiles by headspace solid‐phase microextraction coupled with GC–MS and GC coupled with triple quadrupole MS/MS and a calculation of odor activity values (OAVs) indicated 23 volatiles with OAVs above 1. Ethyl hexanoate showed the highest OAV with 208.8, followed by (E)‐β‐damascenone (189.0), 3‐mercaptohexanol (60.3), isoamyl acetate (45.4), and furaneol (40.1). The aroma of the sweet wine was successfully reconstituted by combining 42 aroma compounds in a model wine solution. 3‐Mercaptohexanol, (E)‐β‐damascenone, furaneol, γ‐octalactone + γ‐decalactone + γ‐hexalactone, and ethyl cinnamate had important influence on the aroma of sweet Petit Manseng wine assessed by omission tests. Moreover, the discrimination of wines from three regions was successfully achieved by partial least squares discriminant analysis based on quantitative results of key odorants. 3‐Mercaptohexanol was considered as the most responsible for the region discrimination and had highest concentrations in Petit Manseng wines from Jiaodong Peninsula. Practical Application: Understanding of the knowledge in key odorants of Petit Manseng wines could be useful to improve wine quality through viticultural and enological practices.